Effects of choline containing phospholipids on the neurovascular unit: A review - Roy, Proshanta; Tomassoni, Daniele; Nittari, Giulio; Traini, Enea; Amenta, Francesco (Frontiers in Cellular Neuroscience, 2022)
The roles of choline and of choline-containing phospholipids (CCPLs) on the maintenance and progress of neurovascular unit (NVU) integrity are analyzed. NVU is composed of neurons, glial and vascular cells ensuring the correct homeostasis of the blood-brain barrier (BBB) and indirectly the function of the central nervous system. The CCPLs phosphatidylcholine (lecithin), cytidine 5’-diphosphocholine (CDP-choline), choline alphoscerate or -glyceryl-phosphorylcholine (GPC) contribute to the modulation of the physiology of the NVU cells. A loss of CCPLs contributes to the development of neurodegenerative diseases such as Alzheimer's disease, multiple sclerosis, Parkinson's disease. Our study has characterized the cellular components of the NVU and has reviewed the effect of lecithin, of CDP-choline and GPC documented in preclinical studies and in limited clinical trials on these compounds. The interesting results obtained with some CCPLs, in particular with GPC, probably would justify reconsideration of the most promising molecules in larger attentively controlled studies. This can also contribute to better define the role of the NVU in the pathophysiology of brain disorders characterized by vascular impairment.